Optimized Dosing Regimens of Meropenem in Septic Children Receiving Extracorporeal Life Support - Wang, Yixue; Chen, Weiming; Huang, Yidie; Wang, Guangfei; Li, Zhiping; Yan, Gangfeng; Chen, Chao; Lu, Guoping (Frontiers in Pharmacology, 2021)
Objectives: To develop a population pharmacokinetic model of meropenem in children with sepsis receiving extracorporeal life support (ECLS) and optimize the dosage regimen based on investigating the probability of target attainment (PTA). Methods: The children with sepsis were prospectively enrolled in a pediatric intensive care unit from January 2018 to December 2019. The concentration-time data were fitted using nonlinear mixed effect model approach by NONMEM program. The stochastic simulation considering various scenarios based on proposed population PK model were conducted, and the PTAs were calculated to optimize the dosage regimens. Results: A total of 25 children with sepsis were enrolled, of whom13 received ECMO, 9 received CRRT, and 4 received ECMO combined with CRRT. 12 children received a two-step 3-hour infusion and 13 children received 1-hour infusion. Bodyweight and creatinine clearance had significant impacts on the PK parameters. ECMO intervention was not related to the PK properties. If 100%T>MIC was chosen as target, children receiving 40mg/kg q8h over a 3h-infusion only reached the PTA up to 77.4%. If bacteria with MIC 2mg/L were to be treated with meropenem and the PTA target was 50%T>MIC, a dose of 40mg/kg q8h for 1h infusion would be necessary. Conclusions: The PK properties of meropenem in septic children receiving extracorporeal life support were best described. We recommended the opitimized dosing regimens for septic children receiving ECLS depending on the PTA of PK target 50%T>MIC and 100%T>MIC, for children with sepsis during ECLS with different body weight, eCrCL and MIC of bacteria. Trial registration: http://www.chictr.org.cn/index.aspx, ChiCTR-OPC-16008703. Registered on 19 June 2016.